2005
DOI: 10.1111/j.1365-2044.2005.04182.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of thoracic epidural anaesthesia during induction of anaesthesia: an investigation into the effects of tracheal intubation during target‐controlled infusion of propofol*

Abstract: SummaryWe compared haemodynamic changes following induction of anaesthesia with propofol during tracheal intubation with and without epidural anaesthesia. Nineteen patients were divided into two groups to receive epidurally administered saline (Group C) or lidocaine 1.5% (Group E). The propofol infusion was started to produce blood concentrations of 3 lg.ml )1 , and following fentanyl and vecuronium administration, tracheal intubation was performed. Mean arterial blood pressure (MBP), heart rate (HR), Bispectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Both 1.5% lidocaine and 0.5% ropivacaine were associated with a reduced increase in MABP post-intubation. Our findings of hemodynamic changes during general anesthesia combined epidural/general anesthesia are consistent with the recent work of Nakatani et al(2005). The mechanism of hemodynamic changes caused by laryngoscopy and intubation is considered to be somato-visceral reflexes (Hassan et al, 1991), associated with catecholamines releasing from the adrenal gland.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both 1.5% lidocaine and 0.5% ropivacaine were associated with a reduced increase in MABP post-intubation. Our findings of hemodynamic changes during general anesthesia combined epidural/general anesthesia are consistent with the recent work of Nakatani et al(2005). The mechanism of hemodynamic changes caused by laryngoscopy and intubation is considered to be somato-visceral reflexes (Hassan et al, 1991), associated with catecholamines releasing from the adrenal gland.…”
Section: Discussionsupporting
confidence: 81%
“…Laryngoscopy and tracheal intubation are thought to be the strongest noxious stimuli during the course of general anesthesia and are often associated with hemodynamic changes including tachycar-dia, hypertension and increases in the plasma concentration of catecholamines (Shribman et al, 1987;Achola et al, 1988). Nakatani et al(2005) investigated hemodynamic changes following induction of anesthesia with propofol during tracheal intubation with or without epidural anesthesia and found that epidural anesthesia did not produce profound hypotentension following induction of anesthesia and produced a reduction in the hemodynamic response to tracheal intubation during a target controlled infusion of propofol.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was caused by the fact that the sympathetic efferent nerve fibres governing the thoracic and abdominal vascular bed originate from the spinal cord between T1 and T3. A thoracic epidural anaesthesia blocks the splanchnic sympathetic nerves in this region and this sympathetic nerve blocking effect antagonizes the sympathetic-catecholamine source vasoconstriction caused by surgical stress, expands part of the vessels, and reduces the quantity of catecholamine released into blood from sympathetic nerve endings (15)(16)(17). Furthermore, the GEA group had a markedly better analgesic effect than the GA group and the latter group had to add the dosages of propofol and fentanyl and increase the concentration of inhaled sevoflurane to meet the requirements for the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgson and Liu [2] applied TES to patients who received epidural or intravenous lidocaine or epidural saline, and found that lidocaine epidural anesthesia reduced the minimum alveolar concentration of sevoflurane by 50%. We also found that thoracic epidural anesthesia decreased hemodynamic changes during induction of anesthesia using propofol in target-controlled infusion [12].…”
Section: Discussionmentioning
confidence: 94%